PENGARUH ENZIM PROTEASE PAPAIN DALAM PAKAN BUATAN TERHADAP PERTUMBUHAN DAN NET PROTEIN UTILIZATION BENIH LELE SANGKURIANG YANG DIBUDIDAYA DI DESA WONOSARI, KECAMATAN BONANG, KABUPATEN DEMAK - Johannes Hutabarat; Diana Rachmawati; Istiyanto Samidjan (Fakultas Perikanan Universitas Pekalongan, 2017)
Availability of diet in Sangkuriang catfish (Clarias gariepinus) cultivation is becoming a main concern. One of the problems in the artificial diet is that the protein content could not fully be utilized by the catfish. To solve the problem is by adding papain protease in the artificial diet. This study was conducted to evaluate the effect of papain protease enzyme in artificial diet on diet utilization efficiency and growth performance of sangkuriang catfish (Clarias gariepinus) fingerlings in the Village of Tambaksari, Sub-district of Rowosari, District of Kendal, and Central Java. The fingerlings with initial body weight averaging 4.23±0,30 g were cultivated with the density of 1 fingerling per liter. The fingerlings were obtained from Center for Hacthery, Muntilan. The fingerlings were fed with artificial diet in four different doses of papain enzyme: A (0%), B (0.75%), C (1.5%), and D (2.25%). The experiment used Complete Random Design with 4 (four) treatments and each treatment replicated 3 (three) times. The results show that the addition of papain protease enzyme significantly (P<0.01) affected on the spesific growth rate (SGR) and net protein utilization (NPU). It could be concluded that the addition of papain protease enzyme could increase the specific growth rate (SGR) and net protein utilization (NPU) of Sangkuriang catfish (Clarias gariepinus) fingerlings. Optimum papain protease enzyme dose on the specific growth rate was 2.25% per kg diet. The water quality during study was still in the viable ranges for Sangkuriang catfish (Clarias gariepinus) fingerlings cultivation.Key word: papain protease enzyme, artificial diet, growth, sangkuriang catfish fingerlings